Predation and Resource Availability Interact to Drive Life-History Evolution in an Adaptive Radiation of Livebearing Fish - Hulthén, Kaj; Hill, Jacob S.; Jenkins, Matthew R.; Langerhans, Randall Brian (Frontiers in Ecology and Evolution, 2021)
Predation risk and resource availability are two primary factors predicted by theory to drive the evolution of life histories. Yet, disentangling their roles in life-history evolution in the wild is challenging because (1) the two factors often co-vary across environments and (2) environmental effects on phenotypes can mask patterns of genotypic evolution. Here, we use the model system of the Post-Pleistocene radiation of Bahamas mosquitofish (Gambusia hubbsi) inhabiting blue holes to provide a strong test of the roles of predation and resources in life-history evolution, as the two factors do not co-vary in this system and we attempted to minimize environmental effects by raising eight populations under common laboratory conditions. We tested a priori predictions of predation- and resource-driven evolution in five life-history traits. We found that life-history evolution in Bahamas mosquitofish largely reflected complex interactions in the effects of predation and resource availability. High predation risk has driven the evolution of higher fecundity, smaller offspring size, more frequent reproduction, and slower growth rate—but this predation-driven divergence primarily occurred in environments with relatively high resource availability, and the effects of resources on life-history evolution was generally greater within environments having high predation risk. This implies that resource-driven selection on life histories overrides selection from predators when resources are particularly scarce. While several results matched a priori predictions, with the added nuance of interdependence among selective agents, some did not. For instance, only resource levels, not predation risk, explained evolutionary change in male age at maturity, with more rapid sexual maturation in higher-resource environments. We also found faster (not slower) juvenile growth rates within low-resource and low-predation environments, probably caused by selection in these high-competition scenarios favoring greater growth efficiency. Our approach, using common-garden experiments with a natural system of low- and high-predation populations that span a continuum of resource availability, provides a powerful way to deepen our understanding of life-history evolution. Overall, it appears that life-history evolution in this adaptive radiation has resulted from a complex interplay between predation and resources, underscoring the need for increased attention on more sophisticated interactions among selective agents in driving phenotypic diversification.